Data analytics & visualization all-in-one - Hyman, Jack A.; Massaron, Luca; McFedries, Paul; Mueller, John Paul; Pierson, Lillian; Reichental, Jonathan; Schmuller, Joseph; Simon, Alan; Taylor, Allen G. (For dummies, 2024)
Data Analytics & Visualization All-in-One For Dummies collects the essential information on mining, organizing, and communicating data, all in one place. Clocking in at around 850 pages, this tome of a reference delivers eight books in one, so you can build a solid foundation of knowledge in data wrangling. Data analytics professionals are highly sought after these days, and this book will put you on the path to becoming one. You'll learn all about sources of data like data lakes, and you'll discover how to extract data using tools like Microsoft Power BI, organize the data in Microsoft Excel, and visually present the data in a way that makes sense using a Tableau. You'll even get an intro to the Python, R, and SQL coding needed to take your data skills to a new level. With this Dummies guide, you'll be well on your way to becoming a priceless data jockey.